Peran Sektor Transportasi Terhadap Perekonomian - Kuswati, Atik S (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2012)
ABSTRACTEconomic growth is closely related to the sustainable development in the transport sector. This relationship is de111onstrated lnj the role of the transport sector which opens the isolation of an area that will proivide a significant economic impact for the welfare of tile people in the region.fudging from tlze contributions, the ven; small contribution of the transport sector to gross do111estic product i11 2005 is 3.97, increasing to 4.28 in 2006, and decreased to 3.24 in 2009. Hai.'i11g i.'icwed from tl1e 111ai11 social fu11ctio11 r.ulziclz consists of 7 groups, the pattenz formationtlzat lzas the lmvest GDP are electricity, gas and water for 46,823 or 0.83%. Transportation was ranked fourth at 181 616, or 3.24%. The average increase in the transport sector over the next five years at 13. 72 % .Key Words: transportation, economic growth